Ukraine : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting and auditing practices in Ukraine, within the broader context of institutional capacity available, for ensuring high-quality financial reporting. Since its independence in 1991, Ukraine has made commendable progress regarding accounting and auditing standards, especially in the banking sector. Nonetheless, gaps exist between Ukrainian and International Accounting Standards (IAS), whereby compliance with Ukrainian accounting standards do not result in the same level of transparency, and comparability in financial statements that IAS mandates. These gaps include accounting standards applicable to commercial, and industrial enterprises (especially disclosure requirements), insurance companies, and, to a lesser extent, credit institutions. In addition, several instances of non-compliance in the application of Ukrainian Accounting Standards were noted. These were compounded by sometimes ineffectual mechanisms for enforcing compliance. Compliance gaps were noted in all sectors, although compliance by large credit institutions appears to be better than average. Although Ukrainian Standards on Auditing were assessed to be largely consistent with International Standards on Auditing (ISA), the analysis detected some important differences. Furthermore, the legal auditing framework is unclear, and sometimes conflicts with the auditing standards. In addition, the assessment detected instances of non-compliance with Ukrainian Standards on Auditing; in this regard, the existing enforcement mechanisms require improvement. Immediate steps are recommended to ensure effective enforcement of established statutory requirements and auditing standards. The report provides policy recommendations, specifically focusing on strengthening enforcement mechanisms to ensure compliance with established accounting and auditing requirements. Moreover, suggestions have been made for important elements of a regulatory framework for the auditing profession, namely, restructuring the statutory regulator of the auditing profession under an effective governance structure.